Optimasi Biaya Pengiriman Kelapa Menggunakan Model Transportasi - Rani, Rani; Rini, Ratih Setyo; Hussaen, Saddam; Azizah, Ayu (TIN: Terapan Informatika Nusantara, 2024)
Transportation problems are usually related to the distribution of goods and services from various production centers to several sales locations or consumers. and the distribution of coconuts is very important for its transportation from 3 existing warehouses to the specified market destination with an initial transportation cost of Rp. 250,000, using and the initial solution for the transportation cost of coconut distribution using the NorthWestCorner (NWC) model is Rp. 82,000. Having a lower difference of Rp. 168,000 with the previous coconut distribution transportation cost, the Least Cost (LC) Method model is Rp. 83,000. Having a lower difference of Rp. 187,000 with the coconut distribution transportation cost, the Vogel Approximation Method (VAM) model is Rp. 86,000. Having a lower difference of Rp. 164,000 with the coconut distribution transportation cost, the Vogel Approximation (VAM) method is Rp. 86,000. Having a lower difference of Rp.164,000 with the cost of coconut distribution transportation, so from all calculations to find out transportation costs, it can optimize transportation costs and also get different results for each method used from the calculations that have been described above. This concludes that there are several methods that can be used to be a means of transportation. Coconut entrepreneurs must think about being able to optimize costs, operational efficiency, flexibility of adjustment, from each price tested in this study.